Hyperferritinemia in patients with nonalcoholic fatty liver disease - Barros,Raffaelle K (2017)
Summary Objective: In liver diseases, hyperferritinemia (HYF) is related to injured cells in acquired and genetic conditions with or without iron overload. It is frequent in patients with nonalcoholic fatty liver disease (NAFLD), in which it is necessary to define the mean of HYF to establish the better approach for them. The present study evaluated the significance of elevated ferritin in patients with NAFLD and steatohepatitis (NASH). Method: The review was performed using search instruments of indexed scientific material, including MEDLINE (by PubMed), Web of Science, IBECS and LILACS, to identify articles published in Portuguese, English and Spanish, from 2005 to May, 2016. Studies eligible included place and year of publication, diagnose criteria to NAFLD, specifications of serum ferritin measurements and/or liver histopathologic study. Exclusion criteria included studies with patients with alcohol consumption ≥ 20 g/day and other liver diseases. Results: A total of 11 from 30 articles were selected. It included 3,564 patients and they were cross-sectional, retrospective, case series and case-control. The result's analyses showed in 10 of these studies a relationship between ferritin elevated serum levels and NAFLD/NASH with and without fibrosis and insulin resistance. Conclusion: Hyperferritinemia in patients with NAFLD/NASH is associated more frequently with hepatocellular injury than hemochromatosis. These data suggest the relevance to evaluate carefully HYF in patients with NAFLD/NASH to establish appropriate clinical approach.